"Feeling good as hell": Black women and the nuances of fat resistance. Issue 3 (2nd September 2021) - Stewart, Terah J.; Breeden, Roshaunda L.
ABSTRACT: Activism and resistance are two often conflated terms in both academic and social movement discourses. However, the conflation renders invisible the ways oppressed people engage in activism and/or resistance that give nuance to the praxis of the terms. Grounded in Black women's ways of knowing, we explore the philosophical bounds of fat activism and fat resistance and through citing examples of Black women engaged in resistance to body- oppressive structures, we highlight the ways fat people and their accomplices (nonfat and non- fat identifying people) contribute to the collective effort for fat justice. We illuminate potential pathways forward for recognizing a range of actions that contribute to the freedom of fat bodies.